Does Higher Education Quality Matter in the UK? - Arnaud Chevalier (Institute for the Study of Labor (IZA), 2014)
This paper estimates the financial returns to higher education quality in the UK. To account for the selectivity of students to institution, we rely on a selection on observable assumptions. We use several estimates including the Generalised Propensity Score of Hirano and Imbens, which relies on a continuous measure of institutional quality. This highlights that the returns to quality are heterogenous, and mostly driven by high quality institutions. Moving from an institution in the 3rd quality quartile to a top quality institution is associated with a 7% increase in earnings.
Keywords: I22; J31; 330; college quality; returns to education; generalised propensity score